Enhancing Community Policing: Exploring Formal Learning Experiences Among Urban Police Officers - Kyle Znamenak (Adult Education Research Conference, 2024)
This ground theory study investigated the formal learning experiences that enable police officers to acquire knowledge and skills related to community relations in an urban environment.
Keywords: Police; Formal Learning; Community Relations